Prioritization for Plastic Surgery Procedures Aimed to Improve Quality of Life: Moral Considerations. Issue 8 (August 2017) - Selvaggi, Gennaro; Kolby, Lars; Elander, Anna
Abstract : Background: Different health conditions are treated in a Plastic Surgery unit, including those cases whose main goal is to enable patients to feel and integrate better within society and therefore improving quality of life, rather then physical functions. Methods: We discuss moral principles that can be used as a guide for health professionals to revise and create policies for plastic surgery patients presenting with non–life-threatening conditions. Results: A specific anatomical feature is not always an indicator of patient's well-being and quality of life, and therefore it cannot be used as the sole parameter to identify the worst-off and prioritize the provision of health care. A policy should identify who preoperatively are the worst-off and come to some plausible measure of how much they can be expected to benefit from an operation. Policies that do not track these principles in any reliable way can cause discrimination. Conclusions: A patient-centered operating system and patient's informed preferences might be implemented in the process of prioritizing health. In circumstances when the effectiveness of a specific treatment is unproven, professionals should not make assumptions based on their own values.